How An Epistemology Of Ignorance Maintains Wikipedia’s Gender Gap - Frost-Arnold, Karen (AoIR Selected Papers of Internet Research, 2017)
This paper argues that an epistemology of ignorance helps to maintain Wikipedia’s gender gap, despite continued efforts to promote gender balance. Wikipedia’s ‘gender gap’ refers to the consistently low numbers of women editing Wikipedia. It is estimated that between 9% and 16% of Wikipedians are women (Hill and Shaw 2013; Wikimedia Foundation 2011). This paper draws on the epistemologies of ignorance literature and research in HCI to uncover Wikipedian social norms, design features, and background socio-linguistic structures that stymie attempts to close the gender gap. First, Wikipedians espouse informal and formal norms of conduct and content inclusion that are generally viewed as gender-neutral, but which in fact facilitate ignorance of gender-based harassment and exclude content related to women. Second, Wikipedia’s commitment to online anonymity means that Wikipedians’ gender is not readily accessible to those who develop tools to combat the gender gap. In this section, I analyze the promise and limitations of Snuggle, a tool designed to facilitate mentoring of newcomers to Wikipedia (Halfaker, Geiger, & Terveen 2014). Finally, the socio-linguistic structures of English gendered pronouns limit the knowledge that can be attained by another promising solution to the gender gap—an experiment called Passing On, which uses reader-sourcing to create Wikipedia content to increase the coverage of women’s biographies (Matias, Diehl, & Zuckerman 2015). The paper concludes with some suggestions for solutions to these problems.